1989
DOI: 10.1016/0020-7292(89)90475-x
|View full text |Cite
|
Sign up to set email alerts
|

Culture of seminal fluid in infertile men and relationship to semen evaluation

Abstract: Bacterial flora of the seminal fluid and its influence on semen quality, was examined in 225 asymptomatic unselected men. Each semen sample was cultured aerobically, anaerobically, for genital mycoplasmas, and for Chlamydia trachomatis. Semen analysis was made according to standard methods recommended by the W.H.O. All 225 semen samples had microbial isolates. All isolates had colony counts of 10(2) colony forming units (cfu/ml). Thirty-three cases had greater than 10(2) cfu/ml, 85 cases had greater than 10(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
3
17
0
1
Order By: Relevance
“…In a study by Balmelli et al (37), which is the second largest study of bacteriospermia in the literature, with 3,196 infertile males, the Enterococcipositive rate of 6.1% and E. coli-positive rate of 1.7% are very similar to those in this study, where the rates are 8.6% and 2.5% of the total study population, respectively. Sperm concentration, motility, and morphology were not significantly affected in this study's bacteriospermic samples, which has been reported in many other studies investigating bacteriospermia in subfertile patients (38)(39)(40). Although a study by Rodin et al demonstrated that samples with Streptococcus viridans and E. fecalis (but not other bacterial species) negatively affected semen quality (34), the current study did not associate any specific bacterial species (specifically E. fecalis and E. coli) with deterioration in sperm count or quality.…”
Section: Figuresupporting
confidence: 65%
“…In a study by Balmelli et al (37), which is the second largest study of bacteriospermia in the literature, with 3,196 infertile males, the Enterococcipositive rate of 6.1% and E. coli-positive rate of 1.7% are very similar to those in this study, where the rates are 8.6% and 2.5% of the total study population, respectively. Sperm concentration, motility, and morphology were not significantly affected in this study's bacteriospermic samples, which has been reported in many other studies investigating bacteriospermia in subfertile patients (38)(39)(40). Although a study by Rodin et al demonstrated that samples with Streptococcus viridans and E. fecalis (but not other bacterial species) negatively affected semen quality (34), the current study did not associate any specific bacterial species (specifically E. fecalis and E. coli) with deterioration in sperm count or quality.…”
Section: Figuresupporting
confidence: 65%
“…The spread of the patho gen by retrograde ascent into the ejaculatory duct via uri nary reflux can cause prostatovesiculitis and epididymitis [3], C. trachomatis infection may affect fertility by induc ing sperm autoantibodies [4,5] or by impairing sperm quality [6], Screening for the presence of C. trachomatis in the semen of asymptomatic infertile men is, therefore, rel evant. However, the sensitivity of C. trachomatis screen ing by culture of mammalian cell monolayers, enzymelinked immunosorbent assay (ELISA), or direct immuno fluorescence with specific monoclonal antibody is limited [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of latent C. trachomatis on semen quality and urogenital organs is debatable [5,9,10]. There have been few studies on the long-term consequences of persistent asymptomatic C. trachomatis infections of the male genital tract [9].…”
Section: Discussionmentioning
confidence: 99%
“…Gregoriou et al [5] demonstrated that asymptomatic infection in the semen does not significantly affect the count, motility, or morphologic features of the specimen. In this study, no correlation was found between C. trachomatis infection and semen quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation